Photoinduced Synthesis of New Diisochromenochromen-4-ones and Their Antimicrobial Activities - Mohamad Yusuf; Indu Solanki; Payal Jain (The Scientific World Journal)
The diisochromenochromen-4-one 3a-3b, 4a-4c, 5a-6a  & 7 have been prepared from the photocyclization reaction of bischromen-4-one 2a-2e. The later compounds are obtained from the O-alkylation of the suitable 3-hydroxy-2-aryl-4H-chromen-4-one 1a-1e with 4,4′-bischloromethyl-diphenyl in dry acetone, anhydrous K2CO3, and PTC (Bu4N+I−) under refluxing conditions. The structures of compounds 2a-2e, 3a-3b, 4a-4c, 5a-6a  & 7 have been characterized from the rigorous analysis of their IR, 1H-NMR, 13C-NMR, ESI-Mass, and elemental analysis. The antibacterial and antifungal activities of the synthesized products were also evaluated against the Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Aspergillus janus and Penicillium glabrum, respectively. Some of the tested compounds showed significant activity against the above-said microorganisms.